Integrated physiological, biochemical and transcriptomic analyses elucidate the response of alpine plant Lamiophlomis rotata (Benth.) Kudo to Low-Nitrogen stress - Liwen Zhong; Tingju Li; Jiasen Zhang; Jie Zhang; Jielin Zhang; Ling Li; Guopeng Chen; Shihong Zhong; Rui Gu (BMC Plant Biology)
Abstract Lamiophlomis rotata (Benth.) Kudo, an endangered medicinal plant endemic to the Qinghai-Tibet Plateau (altitude of 3100–5000 m), faces conservation challenges due to wild resource scarcity and cultivation difficulties. This investigation employed a gradient nitrogen stress system (N1-N4) with a nitrogen-free control (CK) to decipher its nitrogen adaptation mechanisms. Key findings revealed: (1) superior biomass accumulation, SPAD content, and total nitrogen levels in N1 compared to N4; (2) N4-induced suppression of antioxidant enzymes concurrent with elevated secondary metabolites; (3) transcriptomic perturbations in nitrogen metabolism, monoterpenoid biosynthesis, and photosynthetic pathways; (4) identification of eight nitrogen metabolism-related genes and eight iridoid synthase-associated genes exhibiting stress intensity-dependent expression patterns. Notably, key enzymatic activities (NR, Nrt, CA, GS, FM, DXS, NM) demonstrated unimodal responses peaking at N3 intensity. The species demonstrated nitrogen conservation strategies through enhanced assimilation and metabolic diversion into secondary biosynthesis, providing critical insights for alpine medicinal plant cultivation.